Literatura e saberes indígenas na educação básica em A Cura da Terra, de Eliane Potiguara, 2015 - Araújo, Fabiana Tavares (Universidade Federal do Tocantins, 2023)
The teaching process must be meaningful for students, which requires a substantial investment in methodologies that facilitate learning, engaging them in history and fostering a critical mindset. From this perspective, literature presents itself as a vast universe of masterpieces. However, when it comes to indigenous literature, the educational and productive approach faces political, cultural and social challenges in the current scenario. This work aims to understand indigenous literature, highlighting its contributions to teaching, as well as examining its application in the educational context. In addition, it seeks to emphasize the importance of Eliane Potiguara and her writings for literature, society and teaching, culminating in an analysis of her book "A Cura da Terra". bibliographical and exploratory, with a qualitative bias and a descriptive nature. Furthermore, it involves a content analysis of the book "A Cura da Terra" by Eliane Potiguara. The results obtained through this research point to the remarkable distance to be covered in the path of a culturally rich and impactful education. There is an urgent need to incorporate indigenous culture so that their narratives, experiences and memories are perpetuated over time. Brazilian education demands a curricular reform that provides a deeper contact with the true history of the country's colonization. , rescues a connection with the past that remains present, as it evokes the memories and ancestry of indigenous peoples. These communities, despite the persecution and devastation they have suffered, have never stopped and will never stop preserving their identities. It is through these voices, including those of Eliane Potiguara, that indigenous culture continues to pulsate with life and vigor. Thus, teaching with meaning is an essential challenge in contemporary education. Indigenous literature, with its ability to connect past and present, offers a unique opportunity to enrich learning, promote cultural diversity and contribute to the formation of aware citizens. Through analyzes such as the book "A Cura da Terra", it is clear that the incorporation of indigenous voices in the curriculum is a crucial way of honoring the history and struggles of these communities, ensuring that their identities remain vibrant on the pages of books and in classrooms.